Insights into microbial community profiles associated with electric energy production in microbial fuel cells fed with food waste hydrolysate - Xin, Xiaodong (2021)
Insights of microbial community profiles associated with electric energy production in microbial fuel cells (MFCs) fed with food waste hydrolysate (FWH) were investigated in this study. High power density of 0.173 W/m2 was obtained from FWH which was produced from food waste after the pretreatment with fungal mash at an influent COD concentration of 1.2 g/L. The main genera in the MFCs fed with FWH were found to be Rummeliibacillus, Burkholderia, Enterococcus and Clostridium in anodic biofilms, leading to an electrogenesis efficiency of 0.977 kWh/kg COD higher than those obtained in MFCs with single carbon source feed. The key members in the anodic community responsible for electrogenesis were conceptually identified with their metabolic interactions in MFCs fed with FWH. It appeared that the syntrophic cooperation of fermentative species with exoelectrogens played an essential role in the generation of electric energy via specific microbes in anodic biofilm. The power produced from FWH was positively associated with microbial diversity, intermediate community evenness and abundance of functional genes for bioelectrogenesis.